HE ROLE AND ROLE OF PLANTS IN THE INFRASTRUCTURE OF THE CITY OF FARAGONA. - G.M. Maxsudova; T.E.Usmanova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Anotation.As a result of the glorious efforts to establish a new Uzbekistan and lay the foundation for the third Renaissance, our cities and villages are taking on a modern image, the construction of many social structures gives us all unlimited pride and pride.